Early Second Language Learners, Staff Responsiveness and Child Engagement in the Swedish Preschool Context in Relation to Child Behaviour Characteristics and Staffing - Finnman, Johannes; Danielsson, Henrik; Sjöman, Madeleine; Granlund, Mats; Almqvist, Lena (Frontiers in Education, 2021)
Preschool staffs' responsiveness affects children’s behaviour, their difficulties, and engagement in the preschool context, but children’s behaviour and characteristics also affect staff responsiveness. Early second language learners (L2-learners) have been shown to have more problems with behaviour and emotions and lower engagement in preschool. Being engaged in preschool activities predicts future academic performance, attitude towards school and well-being in the short and long term, and can be promoted by the preschool staff. Knowledge of which factors support engagement in preschool for L2-learners can help prevent, in the early years, negative pathways based on low engagement and problems with behaviour and emotions. This cross-sectional study used data from a longitudinal study to investigate the relationship between child engagement and staff responsiveness as well as how child age, child problems with behaviour and emotions, child group size, and the child:staff ratio impact child engagement and staff responsiveness. The study also investigated whether these relations differ between L2-learners and children learning Swedish as their first language (L1-learners). Preschool staff (N = 611) reported through questionnaires on engagement, age, problems with behaviour and emotions and emotional symptoms of 832 children aged 13–71 months, as well as on staffing and staff responsiveness. With a path analysis extended by multi-group analysis, we found two models suggesting that age, problems with behaviour and emotions and preschool staff responsiveness influence child engagement, irrespective of background. The study also found that child engagement significantly influenced staff responsiveness. The multi-group analysis only weakly supported the hypothesis that the child’s age affects staff responsiveness more strongly for L2-learners. The results indicate that individual children and child groups themselves can affect the responsiveness of their staff, and that children with low engagement risk being neglected. L2-learners are at increased risk since they tend to display lower engagement and more behaviour problems in preschool in general. If not attended to early, the lower engagement already apparent among L2-learners in preschool can create stable patterns of low engagement and problems with behaviour and emotions that extend beyond the preschool years and having negative effects on the children’s later well-being and school performance.